(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article provides a comprehensive analysis of the theoretical foundations, practical mechanisms, and main sources for financing the green economy and green entrepreneurship in Uzbekistan. The legal and institutional framework of green economy policies, the financing system involving both the public and private sectors, and the role of international financial institutions are examined. The analysis identifies existing opportunities, constraints, and prospective directions in the green financing system. Additionally, through a comparative analysis with international experience, effective recommendations are developed for practical implementation in Uzbekistan.